2022
DOI: 10.1021/acs.jpcc.1c10397
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Modeling of Dye Anchoring on (001) γ-Monoclinic WO3 Surfaces: The Role of Oxygen Vacancies

Abstract: Here, we focus on the dye's anchoring mechanism onto the (001) monoclinic WO 3 surface. We present first-principles simulations, based on density functional theory (DFT), to get atomistic insights into the adsorption of three different anchoring groups [benzoic acid (BA), Catechol (Cat), and phenylphosphonic acid (PA)] onto the clean and oxygen-defective (001) WO 3 surfaces, considering implicit solvation effects and dispersion corrections. The results show that both BA and PA preferably adsorb in a molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…[6,[43][44][45] Over the last decades, ab initio investigations have been proven to be a valuable tool for getting atomistic insights into the grafting mechanism of molecular sensitizers onto semiconductor slabs, supporting experiments in optimizing the structure and charge generation properties of dye-semiconductor interfaces and providing fundamental understandings of the relevant phenomena governing the DSSCs functioning. [5,37,39,41,[46][47][48][49][50][51][52][53][54][55][56][57][58] Nevertheless, while a large number of theoretical works have addressed the dye adsorption on the TiO 2 surfaces (see for instance refs. [37,59], and references therein), only a few computational studies have appeared so far on the adsorption of anchoring groups or dyes on p-type semiconducting surfaces.…”
Section: Doi: 101002/pssb202200611mentioning
confidence: 99%
“…[6,[43][44][45] Over the last decades, ab initio investigations have been proven to be a valuable tool for getting atomistic insights into the grafting mechanism of molecular sensitizers onto semiconductor slabs, supporting experiments in optimizing the structure and charge generation properties of dye-semiconductor interfaces and providing fundamental understandings of the relevant phenomena governing the DSSCs functioning. [5,37,39,41,[46][47][48][49][50][51][52][53][54][55][56][57][58] Nevertheless, while a large number of theoretical works have addressed the dye adsorption on the TiO 2 surfaces (see for instance refs. [37,59], and references therein), only a few computational studies have appeared so far on the adsorption of anchoring groups or dyes on p-type semiconducting surfaces.…”
Section: Doi: 101002/pssb202200611mentioning
confidence: 99%
“…Given these appealing advantages as a standalone or combined photocatalyst in various heterojunctions, WO 3 has been the subject of many experimental and theoretical studies in recent years. In particular, the solid/liquid interfacial properties, crucial for the efficiency of photocatalytic processes, have been theoretically investigated in the case of the WO 3 /water interface. ,, Previous computational studies have indeed addressed the fundamental understanding of the adsorption of water molecules on the γ-(001) surface [hereafter indicated as (001)]. ,,, Most of the reported studies have shown that water adsorbs preferentially in a molecular (undissociated) form since under-coordinated W atoms at the (001) surface are Lewis acids able to coordinate a water molecule …”
Section: Introductionmentioning
confidence: 99%